Early detection of student degree-level academic performance using educational data mining - Meghji,Areej Fatemah; Mahoto,Naeem Ahmed; Asiri,Yousef; Alshahrani,Hani; Sulaiman,Adel; Shaikh,Asadullah (PeerJ Computer Science, 2023)
Higher educational institutes generate massive amounts of student data. This data needs to be explored in depth to better understand various facets of student learning behavior. The educational data mining approach has given provisions to extract useful and non-trivial knowledge from large collections of student data. Using the educational data mining method of classification, this research analyzes data of 291 university students in an attempt to predict student performance at the end of a 4-year degree program. A student segmentation framework has also been proposed to identify students at various levels of academic performance. Coupled with the prediction model, the proposed segmentation framework provides a useful mechanism for devising pedagogical policies to increase the quality of education by mitigating academic failure and encouraging higher performance. The experimental results indicate the effectiveness of the proposed framework and the applicability of classifying students into multiple performance levels using a small subset of courses being taught in the initial two years of the 4-year degree program.
Keywords: Educational data mining; Classification; Student performance prediction; Data mining; Classification; Student performance prediction; Decision tree; Pedagogical policy